Toxicological mode of action of ZnO nanoparticles: Impact on immune cells. Issue 2 (February 2015) - Roy, Ruchi; Das, Mukul; Dwivedi, Premendra D.
Graphical abstract Overview of ZnO nanoparticles biodistribution and its toxicological mode of action.